How job crafting can link demographic similarity and engagement - Beer, Lynn (Kansas State University, 2021)
In the fast-changing world of business today, employees are not passive recipients of their jobs; instead, employees actively craft their jobs. The concept of job crafting was first developed in 2001 as a way to assess the extent to which this crafting occurs (Wrzesniewski & Dutton). Built within the job crafting framework is the consideration of a person by situation interaction. From that, this study tries to explore how relational demography of the supervisor-subordinate relationship might differentially impact engagement through job crafting. A conditional indirect effect of relational demography was found on engagement through job crafting for minorities, but not White employees. This effect was examined for sex differences, but no relationship was found. Future research needs to further examine these relationships to better understand why this effect occurs and the impact it might have on job crafting related interventions.
Keywords: Job crafting; Relational demography; Engagement